Bacterial and fungal ventilator associated pneumonia in critically ill COVID-19 patients during the second wave - Takwa E. Meawed; Sherweet M. Ahmed; Sherif M.S. Mowafy; Ghada M. Samir; Reham H. Anis (Elsevier, 2021)
Background: The pandemic of coronavirus disease (COVID-19) has caused huge number of patients admitted to intensive care units (ICUs) in a critical need to mechanical ventilation. Ventilator associated pneumonia (VAP) has been noticed as a common complication in these patients with unfavorable outcomes. The current study aimed to assess bacterial and fungal VAP in COVID-19 patients admitted to ICUs during the second wave and to identify the possible risk factors. Methods: Respiratory samples were collected from 197 critically ill COVID-19 patients under mechanical ventilation. Bacterial and fungal superinfections were diagnosed by microbiological cultures with subsequent antimicrobial susceptibility testing of the isolates using available kits. Results: All specimens 197/197 (100%) were positive for bacterial infections, while fungal elements were detected in 134/197 (68%) of specimens. The most frequently isolated bacteria were pan drug resistant (PDR) Klebsiella pneumoniae (41.1%), followed by multi drug resistant (MDR) Acinetobacter baumannii (27.4%). On the other hand, Candida species represented the most frequently isolated fungi (75.4%) followed by molds including Aspergillus (16.4%) and Mucor (8.2%) species.Possible risk factors for fungal VAP included underlying diabetes mellitus (95% confidence interval [CI] 1.09−3.31; p = 0.02), chest disease (95% CI 1.01−3.32; p = 0.05), hypothyroidism (95% CI 1.01−4.78; p = 0.05), and longer duration of mechanical ventilation (p < 0.001). Furthermore, all patients 134/134 (100%) who developed fungal VAP, were already under treatment with corticosteroids and Tocilizumab. Conclusion: Bacterial and fungal VAP in critically ill COVID-19 patients is a serious problem in the current pandemic. Urgent and strategic steps to keep it under control are compulsory.